Oscillatory Behavior of Second Order Neutral Dierence Equations with Mixed Neutral Term - Angayarkanni, M; Kavitha, S (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, we study the oscillatory behavior of solution of second order neutral dierence equation with mixed neutral term of the form (an(zn)) + qnx(n) = 0; n 2 N0; where zn = xn + bnxnô€€€l + cnxn+k and 1P s=n0 1 as = 1. We obtain some new oscilla-tion criteria for second order neutral dierence equation. Examples are presented to illustrate the main results.